Antibiotic prescribing in UK out-of-hours primary care services: a realist-informed scoping review of training and guidelines for healthcare professionals - Alves, PG; Hayward, G; Leydon, G; Barnes, R; Woods, C; Webb, J; Booker, M; Ireton, H; Latter, S; Little, P; Moore, M; Nicholls, C-L; et al. (Royal College of General Practitioners, 2021)
Background Antibiotic overuse has contributed to antimicrobial resistance, which is a global public health problem. In the UK, despite the fall in rates of antibiotic prescription since 2013, prescribing levels remain high in comparison with other European countries. Prescribing in out-of-hours (OOH) care provides unique challenges for prudent prescribing, for which professionals may not be prepared. Aim To explore the guidance available to professionals on prescribing antibiotics for common infections in OOH primary care within the UK, with a focus on training resources, guidelines, and clinical recommendations. Design & setting A realist-informed scoping review of peer-reviewed articles and grey literature. Method The review focused on antibiotic prescribing OOH (for example, clinical guidelines and training videos). General prescribing guidance was searched whenever OOH-focused resources were unavailable. Electronic databases and websites of national agencies and professional societies were searched following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards. Findings were organised according to realist review components, that is, mechanisms, contexts, and outcomes. Results In total, 46 clinical guidelines and eight training resources were identified. Clinical guidelines targeted adults and children, and included recommendations on prescription strategy, spectrum of the antibiotic prescribed, communication with patients, treatment duration, and decision-making processes. No clinical guidelines or training resources focusing specifically on OOH were found. Conclusion The results highlight a lack of knowledge about whether existing resources address the challenges faced by OOH antibiotic prescribers. Further research is needed to explore the training needs of OOH health professionals, and whether further OOH-focused resources need to be developed given the rates of antibiotic prescribing in this setting.